1983
DOI: 10.1111/j.1600-0447.1983.tb11115.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of zimeldine and amitriptyline on car driving and psychomotor performance

Abstract: ABSTRACT— The development of an objective measure of car driving performance, brake reaction time (BRT), is described, and the effects of amitriptyline and zimeldine on this measure are compared in a placebo‐controlled, acute, single dose, volunteer study.The effects of treatment on laboratory tests of critical flicker fusion (CFF) threshold, choice reaction time (CRT) and tracking accuracy and on self‐assessments of sedation are also examined. At 2 hours post‐treatment, amitriptyline produced a significant in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
1

Year Published

1993
1993
1997
1997

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 3 publications
5
53
1
Order By: Relevance
“…Fengabine had a neutral effect throughout the test battery. Due to the fact that the detrimental effects of amitriptyline have been well documented (Hanks, 1984;Hindmarch et al, 1983Hindmarch et al, , 1988Hindmarch & Subhan, 1986) and that these tests have previously been shown to be valid and reliable indicators of drug effects (Hindmarch et al, 1990b(Hindmarch et al, , 1991, it can be concluded that, as fengabine 200 mg and 400 mg has no significant effect on the test battery when compared to placebo, it has very low potential for behavioural toxicity in elderly patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Fengabine had a neutral effect throughout the test battery. Due to the fact that the detrimental effects of amitriptyline have been well documented (Hanks, 1984;Hindmarch et al, 1983Hindmarch et al, , 1988Hindmarch & Subhan, 1986) and that these tests have previously been shown to be valid and reliable indicators of drug effects (Hindmarch et al, 1990b(Hindmarch et al, , 1991, it can be concluded that, as fengabine 200 mg and 400 mg has no significant effect on the test battery when compared to placebo, it has very low potential for behavioural toxicity in elderly patients.…”
Section: Discussionmentioning
confidence: 99%
“…Tracking test This interactive task of psychomotor function entailed tracking a moving arrow on a VDU screen, using a joystick (Hindmarch et al, 1983). The response measure (RMS) is the mean deviation from the track program over the 1 min trial period, with lower scores indicating more accurate tracking.…”
Section: Assessmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Whereas the psychometric methods so far described measure relatively simple sensory and psychomotor func tions, Hindmarch et al [12,13] stress the importance of multidimensional complex experimental setups which are needed for examination of drug effects on daily activities such as car driving for reasons of environmental validity. Such setups as a rule consist of a driving simulator (CAR) in which different complex coordination jobs must be done the individual components of which are derived from the above described methods.…”
Section: Psychometric Methods For Evaluating the Side Effect Profile mentioning
confidence: 99%